Lecturers' Strategies in Optimizing Motivation for Writing Scientific Publications Among Students of the Elementary Madrasah Teacher Education Study Program - Mukhtar Latif; Wanada Siti Salsabilah (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to explore in depth the strategies implemented by a lecturer at the Muhammad Azim Islamic Institute in Jambi in optimizing student writing motivation for scientific publication purposes. Methodology: The approach used was qualitative with a phenomenological design, with one key informant selected through purposive sampling based on verified experience and track record of scientific writing guidance. Data collection was conducted through in-depth semi-structured interviews referring to interview guidelines with four main dimensions: intrinsic motivation, extrinsic motivation, technical guidance strategies, and evaluation and obstacles. Main Findings: The results of the study revealed that the lecturer's strategy was built on five mutually supporting pillars: (1) strengthening intrinsic motivation through instilling career awareness and sharing personal narratives; (2) providing structured academic appreciation and incentives as a reinforcement of extrinsic motivation; (3) implementing guided autonomy in topic selection and collaborative writing as a means of real learning; (4) gradual scaffolding accompanied by growth-oriented feedback; and (5) the introduction of digital tools and artificial intelligence that are relevant to Generation Z. Novelty/Originality of this study: These findings confirm that warm interpersonal relationships between lecturers and students are the main foundation that determines the effectiveness of all motivational strategies implemented.